2021
DOI: 10.4046/trd.2020.0093
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Patients with Multidrug-Resistant Tuberculosis: Comparison of Pre- and Post-Public–Private Mix Periods

Abstract: Background This study compared the treatment outcomes of patients with multidrug-resistant tuberculosis (MDR-TB) before and after the implementation of public–private mix (PPM). Factors affecting treatment success were also investigated. Methods Data from culture-confirmed pulmonary MDR-TB patients who commenced MDR-TB treatment at Pusan National University Hospital between January 2003 and December 2017 were retrospectively reviewed. Patients were divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
2
14
1
Order By: Relevance
“…The overall treatment outcome observed in the present study (65%) was relatively lower than a recent national study report (75.7%). 51 Moreover, other studies also indicated a relatively higher treatment success rates in various settings: 82.4% (Taiwan), 52 75.8% (Pakistan), 53 72.7% (Korea), 54 75.7% (Tanzania). 55 However, it is higher than that reported by WHO (57%) in 2017, 56 a meta-analysis (61%) 57 and an Indonesian national (48%) as well as provincial (36%) study.…”
mentioning
confidence: 94%
“…The overall treatment outcome observed in the present study (65%) was relatively lower than a recent national study report (75.7%). 51 Moreover, other studies also indicated a relatively higher treatment success rates in various settings: 82.4% (Taiwan), 52 75.8% (Pakistan), 53 72.7% (Korea), 54 75.7% (Tanzania). 55 However, it is higher than that reported by WHO (57%) in 2017, 56 a meta-analysis (61%) 57 and an Indonesian national (48%) as well as provincial (36%) study.…”
mentioning
confidence: 94%
“…We thank Oki Nugraha Putra and colleagues [ 1 ] for their comments on our article reporting the impact of public-private mix on the treatment outcomes of patients with multidrug-resistant tuberculosis (MDR-TB) [ 2 ]. Multivariate analysis showed that the use of bedaquiline or delamanid for ≥1 month increased the treatment success rate of patients with MDR-TB.…”
mentioning
confidence: 99%
“…In this issue of the journal, Kang et al [ 7 ] evaluated the impact of the PPM collaboration on MDR-TB control by comparing the treatment outcomes in patients with MDR-TB before and after the implementation of the PPM collaboration. Of 176 patients with pulmonary MDR-TB, 128 patients (72.7%) were successfully treated; the treatment success rate was significantly higher in the post-PPM period than in the pre-PPM period.…”
mentioning
confidence: 99%
“…The PPM collaboration could play an important role in controlling these problems through close monitoring of patients with TB by monitoring treatment compliance and adverse drug reactions and providing education and counselling. The study by Kang et al [ 7 ] shows the positive results of the PPM collaboration in treatment of patients with MDR-TB, indicating the importance of the PPM collaboration covering all hospitals treating patients with TB and providing comprehensive support to patients with TB.…”
mentioning
confidence: 99%
See 1 more Smart Citation